Festival Contemporary Art Visual Games 05 Varna. - Ganevski, Yordan; Varna (Varna : [s.n.], 2005)
Angelov, Angel ; Bugo Corovic, Aladin ; Emilov, Asen ; Karagiozov, Angel ; Schueller, Andrea ; Kirova, Donika ; Cordes, Franziska ; Leitner, Katrin ; Lei, Xui ; et al.
Varna
kunstcatalogus